Certain class of analytic functions defined by q−analogue of Ruscheweyh differential operator - AOUF, Mohamed K.; MOUSTAFA, Adela O.; AL-QUHALI, Fawziah Y. (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In this paper, we obtain coefficient estimates, distortion theorems, radii of close-to-convexity, starlikeness and convexity for functions belonging to the class of analytic starlike and convex functions defined by q−analogue of Ruscheweyh differential operator. Also we find closure theorems, Nk,q,δ (e, g) neighborhood and partial sums for functions in this class. Mathematics Subject Classification (2010): 30C45. Received 07 June 2020; Accepted 06 August 2020